CTA Project Completion Report: Accelerating the Uptake of Climate-smart Agriculture in ACP countries (UPCSA) - Ajayi, Oluyede C. (Technical Centre for Agricultural and Rural Cooperation, 2020)
The impacts of climate change on food security and development in general are well known and have been well documented. ‘Climate Smart Agriculture’ (CSA) has been developed as an approach that helps to achieve “triple wins” in climate actions in agriculture through increased agricultural productivity, adaptation (supporting crops to grow in changing climate conditions), and mitigation (reducing greenhouse gas emissions where possible). Many innovative climate-smart agriculture (CSA) innovations have been developed as solutions to help farmers achieve these triple wins. However, the science of delivery of CSA (actual field level adoption by farmers) has been far lower than the science of discovery (potential impact and technical advancement on CSA), as the mass adoption of these potentially game-changing climate-smart agricultural approaches is not happening at the expected rate. One of the reasons for this is because successful upscaling of these innovations does not depend exclusively on the technical characteristics of the practices, but also on enabling policy and institutional environment; i.e. favourable policies, institutional capacities, and user feedback to continuously refine the CSA. This project seeks to improve resilience, agricultural productivity (food security) and, income of 50,000 smallholder farmers in selected ACP countries through accelerated field uptake of CSA practices using digital agricultural extension approaches and facilitation of multi-stakeholder engagement in appropriate policies to support CSA at various levels.